Influenza in Asthmatics: For Better or for Worse? - Veerapandian, Raja; Snyder, John D.; Samarasinghe, Amali E. (Frontiers in Immunology, 2018)
Asthma and influenza are two pathologic conditions of the respiratory tract that affect millions worldwide. Influenza virus of the 2009 pandemic was highly transmissible and caused severe respiratory disease in young and middle-aged individuals. Asthma was discovered to be an underlying co-morbidity that led to hospitalizations during this influenza pandemic albeit with less severe outcomes. However, animal studies that investigated the relationship between allergic inflammation and pandemic (p)H1N1 infection, showed that while characteristics of allergic airways disease were exacerbated by this virus, governing immune responses that cause exacerbations may actually protect the host from severe outcomes associated with influenza. To better understand the relationship between asthma and severe influenza during the last pandemic, we conducted a systematic literature review of reports on hospitalized patients with asthma as a co-morbid condition during the pH1N1 season. Herein, we report that numerous other underlying conditions such as cardiovascular, neurologic, and metabolic diseases may have been underplayed as major drivers of severe influenza during the 2009 pandemic. This review synopses, 1) asthma and influenza independently, 2) epidemiologic data surrounding asthma during the 2009 influenza pandemic, 3) recent advances in our understanding of allergic host-pathogen interactions in the context of allergic airways disease and influenza in mouse models. Our goal is to showcase possible immunological benefits of allergic airways inflammation as countermeasures for influenza virus infections as a learning tool to discover novel pathways that can enhance our ability to hinder influenza virus replication and host pathology induced thereof.